2021
DOI: 10.18502/kss.v4i15.8197
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perception of Covid 19

Abstract: The purpose of this study was to describe risk perception of Covid 19 in Indonesia. The research was conducted using a survey method with a descriptive quantitative approach. The questionnaire was structured using established theories of risk perception. Questionnaires were compiled on the google form application and distributed via WA. There were 508 participants. The results showed that the participants’ risk perception to Covid 19 was moderate. Most participants were aged between 17 - 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Based on research by (Suhanti et al, [11]) it was found that 42.7% of the study subjects perceived themselves to be at moderate risk, 26.3% at low risk, and 7.3% at high risk.…”
Section: Introductionmentioning
confidence: 97%
“…Based on research by (Suhanti et al, [11]) it was found that 42.7% of the study subjects perceived themselves to be at moderate risk, 26.3% at low risk, and 7.3% at high risk.…”
Section: Introductionmentioning
confidence: 97%
“…27 Medical research showed that the development trajectory of an infectious disease was often determined by the behavior of the individual, which was closely related to the individual's risk perception. [28][29][30] During the epidemic, most people adopted various protective behaviors such as maintaining social distance, washing hands frequently, and disinfecting to avoid contagion. [31][32][33] But many people did not take protective measures, endangering their lives.…”
Section: Introductionmentioning
confidence: 99%
“…The crisis was a significant imposition on the management of organizations, especially service-based organizations. Those affected included workers, customers, owners, suppliers, and all categories of internal and external audiences (Suhanti et al, 2020). Social responsibility has become a major challenge for organizations.…”
Section: Introductionmentioning
confidence: 99%